Keragaman Delapan Anggrek Dendrobium spp. Indonesia Berdasarkan Penanda RAPD - , DHARMESTA ADHIWIRA; , Dr. Ir. Aziz Purwantoro, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Study on diversity among eight Dendrobium spp. orchids is necessary for orchid breeders in order to plant crossing efficiency. Highly similarity among Dendrobium spp. would increase crossing opportunity. The objectives of this study were to grouping orchid genotypes into clusters according to their similarity as measured by DNA banding patterns. Genetic similarity among 10 orchid genotypes were analysed based on 85 bands generated from five RAPD primers. The result showed that genetic diversity within species indicated by percentage of polymorphic loci was in range of 11.76 to 40%. Cluster analysis based on molecular markers showed that the Dendrobiums were divided into six groups at a distance of 7.5 in dendogram, where is first group consisted of D. spectabile and D. macrophyllum, second group consisted of D. lasianthera, third group consisted of D. antennatum, D. discolor, and D. stratiotes, fourth group consisted of D. smillieae and D. crumenatum, fifth group consisted of D. signatum, and sixth group consisted of D. fimbriatum. Two Dendrobium spesies from another country (D. fimbriatum and D. signatum) made a group outside of Dendrobium of Indonesiaâs group, indicating that both spesies have distant genetic similarity with Dendrobium spesies of Indonesia. Result of grouping based on molecular markers is different from grouping based on morphological observation, probably due to environment effects.